Exploring learning & teaching in higher education - Li, Mang; Zhao, Yong (New Frontiers of Educational Research,, 2015)
The focus of this book is on exploring effective strategies in higher education that promote meaningful learning and go beyond discipline boundaries, with a special emphasis on Subjectivity Learning, Refreshing Lecturing, Learning through Construction, Learning through Transaction, Transformative Learning, Using Technology, and Assessment for Learning and Teaching in particular. The research collected in this book is all based on empirical studies and includes research methods and findings that will be of great interest to teachers and researchers in the area of higher education. The main benefit readers will derive from this book is a meaningful insight into what other teachers around the world are doing in higher education and what lessons they have learned, which will support them in their own teaching.   .